RESPON PERTUMBUHAN DAN HASIL TANAMAN SAWI HIJAU (Brassica Juncea L.) AKIBAT PEMBERIAN PUPUK KANDANG SAPI DAN BIOURINE SAPI - I Gusti Ayu Diah Yuniti; I Putu Sujana; I Made Sukerta; Komang Dean Ananda; Oktaviani Nawul (Faculty of Agriculture and Business, Universitas Mahasaraswati Denpasar , Kec. Denpasar Utara, Kota Denpasar, Bali 80233, 2024)
Brassica juncea L. or commonly called mustard greens is one of the most popular types of vegetables in Indonesia, because this mustard is one of the varieties that contain various health benefits. This study aims to determine